CURRENT APPROACHES TO THE LABORATORY DIAGNOSIS OF RHEUMATIC DISEASES: ROLE OF MOLECULAR AND CELLULAR BIOMARKERS - E. N. Aleksandrova; A. A. Novikov; E. L. Nasonov (Научно-практическая ревматология, 2016)
Laboratory medicine in the early 21st century has achieved advances due to the development and prompt practical introduction of innovative molecular cell technologies, which have assisted in increasing the diagnostic sensitivity and specificity of laboratory tests and in substantially expanding the spectrum of study biomarkers in rheumatology. High-technology automated analytical systems using both classical uniplex methods for immunochemical analysis (indirect immunofluorescence test, enzyme immunoassay, immunoblotting, immunodot assay, immunonephelometry, chemiluminescence immunoassay, and radioimmunoassay) and multiplex diagnostic platforms based on DNA, RNA, protein and cellular microchips, polymerase chain reaction, flow cytometry, and mass spectrometry have been used in the past decade to determine biomarkers of rheumatic diseases (RD) in blood, synovial fluid, urine, biopsy specimens of the synovial membrane, kidney, and other affected tissues.Present-day generation of molecular and cellular biomarkers (autoantibodies, acute-phase inflammatory proteins, cytokines, chemokines, vascular endothelial activation markers, immunoglobulins, complement components, lymphocyte subpopulations, osseous and cartilaginous tissue metabolic products, intracellular signaling molecules, proteases, and genetic, epigenetic, and transcriptomic markers) is an important tool for prevention, early diagnosis, assessment of disease activity, progression rate, clinical laboratory subtypes of RD, prediction of the efficiency of therapy and the risk of adverse events during treatment. Deciphering of the key pathogenetic mechanisms of RD could identify the molecular and cellular biomarkers that might be used as therapeutic targets. Biologicals (monoclonal antibodies and hybrid protein molecules) that selectively inhibit proinflammatory cytokines and membrane molecules mediating the pathological activation of immunocompetent cells are successfully used to treat RD today.The alternative therapies of RD include the use of low-molecular-weight chemically synthesized agents that suppress the activity of tyrosine kinases. The important area of this therapy is to restore immunological tolerance and to correct autoimmune disorders by means of autologous hematopoietic stem cells, mesenchymal stromal cells, autologous tolerogenic dendritic cells, regulatory T and B cells, gene therapy, and peptide antigens. The prospects for the laboratory diagnosis of RD are associated with the necessity of harmonizing and standardizing the current methods to determine autoantibodies and with the search for and clinical validation of novel proteomic, transcriptomic, and genomic biomarkers.